(untitled) (Research, Society and Development, 2021)
Mitochondrial diseases constitute an important group of hereditary metabolic disorders with heterogeneous clinical and genetic expression. Therefore, this article aims to characterize the scientific production on mitochondrial diseases. Therefore, an integrative literature review on the subject was carried out. The information obtained was analyzed in the light of Cooper (1984). The category that emerged in the data collection and structured the discussion was: conceptual and critical contributions about mitochondrial diseases. The results show the concentration of studies on mitochondrial diseases in southeastern Brazil. In addition, research has generally highlighted that because mitochondria participate in various cellular processes, it becomes an essential component of the eukaryotic cell and that mutations that compromise its functioning can cause severe damage to the cell, causing so-called diseases mitochondrial diseases, which are the largest known group of inherited diseases, in addition to being related to neurodegenerative diseases.